2021
DOI: 10.2196/26494
|View full text |Cite
|
Sign up to set email alerts
|

Patient Monitoring Alarms in an Intensive Care Unit: Observational Study With Do-It-Yourself Instructions

Abstract: Background As one of the most essential technical components of the intensive care unit (ICU), continuous monitoring of patients’ vital parameters has significantly improved patient safety by alerting staff through an alarm when a parameter deviates from the normal range. However, the vast number of alarms regularly overwhelms staff and may induce alarm fatigue, a condition recently exacerbated by COVID-19 and potentially endangering patients. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The alarm logs were cleaned; only entries describing alarm start were selected, the alarms were categorized in groups depending on the origin of the alarm (electrocardiogram (ECG), ventilator etc. ), as previously described 25 . Only alarms regarding ECG, invasive and non-invasive blood pressure (IBP and NIBP), SpO2, ventilator and temperature were selected since these constitute the basic monitoring requirements for a patient in the ICU.…”
Section: Methodsmentioning
confidence: 99%
“…The alarm logs were cleaned; only entries describing alarm start were selected, the alarms were categorized in groups depending on the origin of the alarm (electrocardiogram (ECG), ventilator etc. ), as previously described 25 . Only alarms regarding ECG, invasive and non-invasive blood pressure (IBP and NIBP), SpO2, ventilator and temperature were selected since these constitute the basic monitoring requirements for a patient in the ICU.…”
Section: Methodsmentioning
confidence: 99%
“…Desensitization to these alarms is defined as alarm fatigue [ 13 ]. According to the results of the Simpson 2019 study, most of the generated alarms are not related to the patient’s clinical condition and despite the immediate response of the nurses, did not help the patient’s clinical evaluation and caused fatigue in the nurses [ 14 ], a condition that has recently been exacerbated by COVID-19 and potentially endangers patient safety [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…HCPs also reported that single rooms improved patients’ sleep. (9) Poncette and colleagues(100) found that fewer alarms raised in shared accommodation reduced overall noise levels. One study also noted that patients preferred single rooms because they felt they were less likely to disturb other patients.…”
Section: Resultsmentioning
confidence: 99%
“…Significantly lower rates of falls were seen in multi-bed accommodation in two studies. (16,22) The study of Poncette et al,(100) which analysed alarm data in an ICU, found that the number of alarms per bed per day was higher in single rooms than in shared accommodation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation